Modele edukacji: neoliberalny, konserwatywny i welfare state – na przykładzie Finlandii i Polski - Suwalska , Arleta (Studia Edukacyjne, 2023)
The article addresses two distinct models of education: Finnish and Polish, taking into consideration the ways of financing education. The research aims to identify the characteristic features of the Polish and Finnish models of education and teachers’ professional status in Finland and Poland. The focus of the study was to analyze relations between the neoliberal and conservative policies in Poland and the welfare state policy in Finland. The next step was to identify how state economy is related to ways of teachers’ educational functioning in Finland and Poland. The paper reveals differing attitudes and patterns which characterize the Finnish and Polish models of education with consequences for teachers’ satisfactory functioning in their profession.